1986
DOI: 10.1111/j.1464-410x.1986.tb05892.x
|View full text |Cite
|
Sign up to set email alerts
|

Rice‐bran Treatment for Calcium Stone Formers with Idiopathic Hypercalciuria

Abstract: The efficacy of rice-bran therapy was studied in patients with hypercalciuria who were suffering from calcium stones. The frequency of stone episodes was reduced dramatically, especially in "active recurrent stone formers". Urinary calcium excretion was considerably reduced, while urinary phosphate and oxalate were slightly increased. Urinary magnesium, uric acid, serum calcium, phosphate, magnesium and uric acid were not affected. There were no changes in serum iron, copper and zinc even when patients were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Consequently, more free oxalate could be available to be absorbed. However, published studies reported that dietary fibre had no effect (Shah et al, 1980;Ala-Opas et al, 1987) or that it resulted in a reduction (Robertson, 1987;Strohmaier et al, 1988) or an increase (Ebisuno et al, 1986) in urinary oxalate excretion. The two vegetarian diets contained almost the same amount of dietary fibre, yet they differed in the phytate content.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, more free oxalate could be available to be absorbed. However, published studies reported that dietary fibre had no effect (Shah et al, 1980;Ala-Opas et al, 1987) or that it resulted in a reduction (Robertson, 1987;Strohmaier et al, 1988) or an increase (Ebisuno et al, 1986) in urinary oxalate excretion. The two vegetarian diets contained almost the same amount of dietary fibre, yet they differed in the phytate content.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental and clinical hypocalciuric effects of dietary fibre have been reported during the last years [15][16][17][18]. These effects have been mainly assigned to the presence of phytate (myo-inositol hexaphosphate) that forms insoluble salts with calcium in the intestine, avoiding its absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Some drugs, such as sodium cellulose phosphate, orthophosphate, and thiazicles, have been shown to be effective means of reducing urinary calcium Correspondence to: N. Wu excretion in hypercalciuric patients and, hence, the incidence of recurrent stone formation [1][2][3]. However, these drugs may induce side effects.During the last decade, the experimental and clinical hypocalciuric effects of rice bran (or wheat bran) have been reported [4][5][6][7][8]. Phytin (inositol hexaphosphate) proves to be the most effective substance of rice-bran treatment and plays an active role in reducing the intestinal absorption of calcium.…”
mentioning
confidence: 99%
“…During the last decade, the experimental and clinical hypocalciuric effects of rice bran (or wheat bran) have been reported [4][5][6][7][8]. Phytin (inositol hexaphosphate) proves to be the most effective substance of rice-bran treatment and plays an active role in reducing the intestinal absorption of calcium.…”
mentioning
confidence: 99%